Perancangan Sistem Informasi Penjualan dan Pemesanan Berbasis Web pada Jadida Butik - Andika Gustiawan; Mutiara Ainun Shafa; Oki Tiara Dewi (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2020)
Jadida Butik is a boutique that sells a variety of fashion items that already have a regular customer and new customers. The increasing number of subscribers, the more data input manually and the expansion of sales for outside other cities. Jadida Butik requires online sales and booking data or can be said to be Online-shop. All customers can access orders online from outside the city.With the utilization and implementation of information technology, data sets interconnected with each other can be organized into a file, where the data is set to be stored in a computer to facilitate the custtomers in accessing data. This information System is indispensable in the world of SMES, especially those concerning ordering. The sales and web-based customer information System in Jadida Butik is used as a means of information for customers and sellers regarding sales data by utilizing computerised system using PHP Web programming language and MySQL database.